Characterization method of polyacrylonitrile fiber skin-core structure
Calculation of the cortical thickness of the polyacrylonitrile fiber tow sample by dissolving and processing the polyacrylonitrile fiber tow sample has solved the problem of characterization in the prior art, and achieved rapid and accurate fiber quality debugging, simplified the process flow and reduced costs.
Patent Information
- Application Number
- CN202411072066.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The prior art is difficult to quickly and accurately characterize the core structure of polyacrylonitrile fibers, which leads to difficulty in fibre quality debugging, and the equipment is expensive, with a long test cycle, making it difficult to promptly guide the process debugging of the production front line.
By dissolving and processing polyacrylonitrile fiber tow samples of different lengths, the relationship between their dissolution depth and time is calculated, the cortical thickness is determined, the core structure is evaluated by the difference in dissolution rate, and the wet spinning process debugging is guided by a simple and low-cost method. .
It achieves rapid and accurate acquisition of fiber cortex thickness data, simplifies process debugging process, reduces equipment costs, and can promptly guide the process adjustment of fiber production, and improves fiber quality.
Smart Images

Figure CN119164834A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fibers, in particular to a method for characterizing the skin-core structure of polyacrylonitrile fibers. Background Art
[0002] Carbon fiber has the characteristics of high specific strength, high specific modulus, heat resistance, corrosion resistance, fatigue resistance, creep resistance, etc. It is a high-performance fiber material and has been widely used in aerospace, national defense construction, sports and leisure products, medical equipment and construction industries. Carbon fiber can be divided into polyacrylonitrile-based, asphalt-based and viscose-based carbon fiber. Among them, polyacrylonitrile-based carbon fiber has the widest application, the largest amount, and the fastest development, and has an absolute advantage in carbon fiber production.
[0003] Polyacrylonitrile fibers (i.e., polyacrylonitrile precursors) prepared by wet spinning technology inevitably have a skin-core structure, that is, the fiber surface structure is dense and the core structure is relatively loose. Among them, if the fiber cortex is thicker and the structural difference between the cortex and the core is large, the fiber quality is low and high-quality polyacrylonitrile-based carbon fibers cannot be produced. With the development of wet spinning technology, researchers have tried to modify the coagulation bath and adjust the coagulation molding process to control the fiber skin-core structure, making the fiber cortex thinner and reducing the difference between the cortex structure and the core structure. As the research deepens, researchers urgently need a convenient, fast, and accurate method for characterizing the fiber skin-core structure so that they can guide process debugging in a timely and efficient manner at the debugging site.
[0004] At present, the characterization methods of fiber skin-core structure include scanning electron microscopy observation and transmission electron microscopy observation. However, the equipment required for scanning electron microscopy and transmission electron microscopy observation is relatively high-end and expensive, and general enterprises rarely have them. When debugging work is carried out on the front line of the process, sampling and external testing are required, which makes the testing cycle long. Therefore, this method is difficult to guide the process debugging of the production line in a timely and efficient manner. In addition, the above methods can only qualitatively characterize the existence of the skin-core structure, and the distinction between the skin and the core layer and the determination of the skin thickness are greatly affected by human factors. Summary of the invention
[0005] In view of this, the present invention provides a method for characterizing the skin-core structure of polyacrylonitrile fibers, the main purpose of which is to provide a timely and easy-to-operate method for characterizing the skin-core structure of fibers.
[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:
[0007] On the one hand, an embodiment of the present invention provides a method for characterizing the skin-core structure of polyacrylonitrile fiber, which comprises the following steps:
[0008] Step 1): taking a plurality of polyacrylonitrile fiber tow samples of a set length from the polyacrylonitrile fiber tow to be characterized; performing a dissolution treatment on the plurality of polyacrylonitrile fiber tow samples, wherein different polyacrylonitrile fiber tow samples have different corresponding dissolution treatment times t; and calculating the dissolution depth H of each polyacrylonitrile fiber tow sample after the dissolution treatment;
[0009] Step 2): According to the relationship between the dissolution depth H and the dissolution treatment time t, the cortical thickness of the polyacrylonitrile fiber is determined.
[0010] Preferably, in step 1):
[0011] The calculation formula of the dissolution depth H is as follows:
[0012] H = r0-r;
[0013] Wherein, r0 is the fiber radius of the polyacrylonitrile fiber tow sample before dissolution treatment;
[0014] r is the fiber radius of the polyacrylonitrile fiber tow sample after dissolution treatment.
[0015] Preferably, the calculation formula of r0 is as follows:
[0016] r0=[X m / (n×1000×ρ×π)] 1 / 2 ×1000;
[0017] Among them, r0 is in μm; X m is the weight of a 1m long polyacrylonitrile fiber tow sample in grams; the polyacrylonitrile fiber tow to be characterized is nk tow; nk means there are n×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 .
[0018] Preferably, the calculation formula of r is as follows:
[0019] r = [W / (n × 1000 × ρ × π)] 1 / 2 ×1000;
[0020] Wherein, r is in μm; W is the fiber mass of the 1m long polyacrylonitrile fiber tow sample after dissolution treatment, and the polyacrylonitrile fiber tow to be characterized is nk tow; nk means that there are n×1000 single fibers in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 Preferably, the step 1) comprises:
[0021] Step 11): taking a plurality of polyacrylonitrile fiber tow samples of a set length from the polyacrylonitrile-based fiber tow to be characterized;
[0022] Step 12): drying a plurality of polyacrylonitrile fiber tow samples; after cooling, placing the plurality of polyacrylonitrile fiber tow samples in different dissolution containers, adding a set amount of solvent into each dissolution container, and dissolving them; wherein different polyacrylonitrile fiber tow samples have different dissolution treatment times; preferably, the mass ratio of the solvent to the polyacrylonitrile fiber tow sample is (400-600):1;
[0023] Step 13) After reaching the corresponding dissolution treatment time, washing, drying, cooling, and weighing the fibers of each polyacrylonitrile fiber tow sample after the dissolution treatment to obtain the fiber mass W of each polyacrylonitrile fiber tow sample after the dissolution treatment;
[0024] Step 14) according to the fiber mass W of the polyacrylonitrile fiber tow sample after the dissolution treatment, respectively calculate the fiber radius r of each polyacrylonitrile fiber tow sample after the dissolution treatment, and further calculate the dissolution depth H of each polyacrylonitrile fiber tow sample after the dissolution treatment;
[0025] Preferably, in step 12), the solvent is selected from one or more of dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and dimethylacetamide (DMAc);
[0026] Preferably, in step 12), during the dissolution treatment, the dissolution container needs to be placed in a constant temperature shaker at 25-30° C. for shaking;
[0027] Preferably, in step 12), the drying temperature is 105-120° C., and the drying time is 1.5-3 h;
[0028] Preferably, in step 13), when washing, first wash with an aqueous solution of DMSO and then wash with running water;
[0029] Preferably, in step 13), the drying temperature is 105-120° C., and the drying time is 2-4 hours.
[0030] Preferably, in step 11):
[0031] The polyacrylonitrile fiber tow to be characterized is an n K tow, where n K means there are n×1000 single filaments in one fiber tow. A tow with a length of 0.1-1 m is taken from the polyacrylonitrile fiber tow to be characterized as a polyacrylonitrile fiber tow sample;
[0032] Preferably, the larger the n value is, the smaller the length of the polyacrylonitrile fiber tow sample is;
[0033] Preferably, a tow with a length of 0.5-1 m is taken as the polyacrylonitrile fiber tow sample;
[0034] Preferably, before the dissolution treatment, the polyacrylonitrile fiber tow sample needs to be cut into segments of 2-3 cm in length and manually opened (the single filaments are manually separated as much as possible to facilitate the dissolution treatment).
[0035] Preferably, in step 12), the dissolution treatment time ranges from 1 to 30 minutes.
[0036] Preferably, the plurality of polyacrylonitrile fiber tow samples of set lengths include a first polyacrylonitrile fiber tow sample, a second polyacrylonitrile fiber tow sample, a third polyacrylonitrile fiber tow sample, a fourth polyacrylonitrile fiber tow sample, a fifth polyacrylonitrile fiber tow sample, a sixth polyacrylonitrile fiber tow sample, a seventh polyacrylonitrile fiber tow sample, an eighth polyacrylonitrile fiber tow sample, a ninth polyacrylonitrile fiber tow sample, and a tenth polyacrylonitrile fiber tow sample; wherein,
[0037] The dissolution treatment time corresponding to the first polyacrylonitrile fiber tow sample is 1-1.2 min, preferably 1 min; the dissolution treatment time corresponding to the second polyacrylonitrile fiber tow sample is 2-2.2 min, preferably 2 min; the dissolution treatment time corresponding to the third polyacrylonitrile fiber tow sample is 3-3.2 min, preferably 3 min; the dissolution treatment time corresponding to the fourth polyacrylonitrile fiber tow sample is 4-4.2 min, preferably 4 min; the dissolution treatment time corresponding to the fifth polyacrylonitrile fiber tow sample is 5-5.2 min, preferably 5 min; the dissolution treatment time corresponding to the sixth polyacrylonitrile fiber tow sample is 5-6 min, preferably 5 min; The dissolution treatment time corresponding to the polyacrylonitrile fiber tow sample is 10-10.5min, preferably 10min; the dissolution treatment time corresponding to the seventh polyacrylonitrile fiber tow sample is 15-15.5min, preferably 15min; the dissolution treatment time corresponding to the eighth polyacrylonitrile fiber tow sample is 20-21min, preferably 20min; the dissolution treatment time corresponding to the ninth polyacrylonitrile fiber tow sample is 25-26min, preferably 25min; the dissolution treatment time corresponding to the tenth polyacrylonitrile fiber tow sample is 29-30min, preferably 30min.
[0038] Preferably, the step 2) comprises:
[0039] Step 21): In a rectangular coordinate system, plotting a data point diagram of the dissolution depth H as a function of the dissolution treatment time t;
[0040] Step 22): according to the distribution of the data points, the data points at the early stage of dissolution are fitted into a first straight line, and the data points at the late stage of dissolution are fitted into a second straight line;
[0041] Step 23): determine the intersection of the first straight line and the second straight line, and record the coordinates of the intersection; determine the value of the dissolution depth corresponding to the intersection as the cortical thickness of the polyacrylonitrile fiber tow to be characterized.
[0042] Preferably, in step 22):
[0043] Preferably, when fitting the data points into the first straight line and the second straight line, the dissolution treatment time range corresponding to the initial dissolution stage and the dissolution treatment time range corresponding to the late dissolution stage are determined according to the distribution characteristics of the data points;
[0044] Preferably, the data points at the initial stage of dissolution refer to data points corresponding to a dissolution treatment time t in the range of ≤5 min; the data points at the late stage of dissolution refer to data points corresponding to a dissolution treatment time t in the range of greater than >5 min and ≤30 min.
[0045] Compared with the prior art, the characterization method of the polyacrylonitrile fiber skin-core structure of the present invention has at least the following beneficial effects:
[0046] The embodiment of the present invention proposes a method for characterizing the skin-core structure of a polyacrylonitrile fiber. It is only necessary to take a plurality of polyacrylonitrile fiber tow samples of a set length from the polyacrylonitrile fiber tow to be characterized, and then perform a dissolution treatment to calculate the dissolution depth H of each polyacrylonitrile fiber tow sample after the dissolution treatment. By making the dissolution treatment time t corresponding to different polyacrylonitrile fiber tow samples different, and then according to the relationship between the dissolution depth H and the dissolution treatment time t, the cortex thickness of the polyacrylonitrile fiber can be determined. It should be noted here that: the characterization method of the present invention is based on the difference in the dissolution rate of the dense structure and the loose structure in the solvent to evaluate the degree of the skin-core structure. The dissolution rate of the dense part of the surface of the tow is slower during the dissolution process, and the more it dissolves into the fiber, the faster the dissolution rate. The present invention defines the transition point from slow to fast dissolution rate as the dissolution rate transition point, and defines the dissolution depth corresponding to the transition point as the fiber cortex thickness (according to the relationship between the dissolution depth H and the dissolution treatment time t, the dissolution depth corresponding to the transition point can be obtained, that is, the fiber cortex thickness). With the help of the cortex thickness index, the degree of the skin-core structure of the fiber can be evaluated. The greater the cortex thickness, the greater the degree of the skin-core structure. Compared with direct observation methods such as scanning electron microscopy and transmission electron microscopy, the method of the present invention is simple to operate, low in cost, more convenient, and can quickly guide on-site debugging of the wet spinning process.
[0047] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a schematic diagram of the variation of dissolution depth (H) with dissolution time (t) provided in Example 2 of the present invention;
[0049] Figure 2 is a schematic diagram showing the variation of the dissolution depth (H) of the fiber with the dissolution time (t) in Example 1 of the present invention;
[0050] Figure 3 is a schematic diagram showing the variation of the dissolution depth (H) of the fiber with the dissolution time (t) in Example 3 of the present invention;
[0051] Figure 4 This is a cross-sectional TEM photograph of a carbon fiber monofilament prepared using the polyacrylonitrile fiber tow sample of Comparative Example 1. DETAILED DESCRIPTION
[0052] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0053] The inventive concept of the present invention is as follows: When preparing polyacrylonitrile fibers by wet spinning, it is difficult to avoid the existence of a skin-core structure in the fibers, where the surface structure of the fibers is dense and the core structure is relatively loose. The present invention evaluates the degree of the skin-core structure based on the difference in dissolution rates of the dense structure and the loose structure in the solvent. During the dissolution process, the dense surface part of the fiber bundle dissolves at a slower rate, and the further it dissolves into the fiber, the faster the dissolution rate. With the help of the dissolution test, the change in the dissolution depth over time during the process of dissolving the fiber from the surface to the inside can be obtained, such as Figure 1 As shown, in the early stage of dissolution, the dissolution depth changes slowly with time, and the test points in the early stage of dissolution are fitted into a straight line, and the slope of the straight line reflects the dissolution depth per unit time in the early stage of dissolution, that is, the initial dissolution rate; in the late stage of dissolution, the dissolution depth changes rapidly with time, and the test points in the late stage of dissolution are fitted into a straight line, and the slope of the straight line reflects the dissolution depth per unit time in the late stage of dissolution, that is, the late dissolution rate; the present invention defines the transition point from slow to fast dissolution rate, that is, the intersection of the fitted straight line of the solvent initial test point and the fitted straight line of the late stage of dissolution test point, as the dissolution rate transition point, and defines the dissolution depth corresponding to the transition point as the fiber cortex thickness. Among them, the greater the fiber cortex thickness, the greater the degree of the skin-core structure.
[0054] The scheme of the present invention is as follows:
[0055] The embodiment of the present invention provides a method for characterizing the skin-core structure of polyacrylonitrile fiber, which comprises the following steps:
[0056] Step 1): taking a plurality of polyacrylonitrile fiber bundle samples of set length from the polyacrylonitrile fiber bundle to be characterized; performing dissolution treatment on the plurality of polyacrylonitrile fiber bundle samples of set length, wherein different polyacrylonitrile fiber bundle samples have different corresponding dissolution treatment times t; and calculating the dissolution depth H of each polyacrylonitrile fiber bundle sample after the dissolution treatment.
[0057] Preferably, the step 1) comprises:
[0058] Step 11): taking a plurality of polyacrylonitrile fiber tow samples of a set length from the polyacrylonitrile-based fiber to be characterized (ie, the plurality of polyacrylonitrile fiber tow samples have the same length).
[0059] If the polyacrylonitrile fiber to be characterized is a 1-6K tow, a tow of 1 m in length is taken from the polyacrylonitrile fiber to be characterized as a polyacrylonitrile fiber tow sample; if the polyacrylonitrile fiber to be characterized is a 12-24 tow, a tow of 0.5 m in length is taken from the polyacrylonitrile fiber to be characterized as a polyacrylonitrile fiber tow sample; if the polyacrylonitrile fiber to be characterized is a 48-60K tow, a tow of 0.1 m in length is taken from the polyacrylonitrile fiber to be characterized as a polyacrylonitrile fiber tow sample.
[0060] Step 12): drying a plurality of polyacrylonitrile fiber bundle samples; after cooling, placing the plurality of polyacrylonitrile fiber bundle samples in different dissolution containers, adding a certain amount of solvent (the mass ratio of the solvent to the polyacrylonitrile fiber bundle sample is 400-600:1) into each dissolution container for dissolution treatment; wherein different polyacrylonitrile fiber bundle samples have different corresponding dissolution treatment times.
[0061] Preferably, before the dissolution treatment, the polyacrylonitrile fiber bundle sample needs to be cut into 2-3 cm length segments. Preferably, the solvent is dimethyl sulfoxide (DMSO); preferably, during the dissolution treatment, the dissolution container needs to be placed in a constant temperature (e.g., 25° C.) shaker for shaking; preferably, the drying treatment temperature is 110° C., and the drying treatment time is 2 hours.
[0062] Step 13) After reaching the corresponding dissolution treatment time, the fibers of each polyacrylonitrile fiber tow sample after the dissolution treatment are washed, dried, cooled, and weighed to obtain the fiber mass W of each polyacrylonitrile fiber tow sample after the dissolution treatment.
[0063] Preferably, the washing method is as follows: first washing with a DMSO aqueous solution, then washing with running water. Further preferably, first washing with DMSO aqueous solutions of 88%, 55%, and 30% by mass fraction in sequence, and finally washing with running water at room temperature for more than 10 minutes.
[0064] Preferably, the drying temperature is 110° C. and the drying time is 2 h.
[0065] Step 14) according to the fiber mass W of the polyacrylonitrile fiber tow sample after the dissolution treatment (when the sample is not a 1m fixed-length sample, it is converted into the fiber mass W of the 1m fixed-length sample after the dissolution treatment, such as: for a 0.5m fixed-length sample, the fiber mass after the dissolution treatment is multiplied by 2, and the mass W after the dissolution treatment when the fixed length is 1m can be converted), the fiber radius r of each polyacrylonitrile fiber tow sample after the dissolution treatment is calculated, and the dissolution depth H of each polyacrylonitrile fiber tow sample after the dissolution treatment is further calculated;
[0066] The calculation formula of the fiber radius r of each polyacrylonitrile fiber tow sample after dissolution treatment is as follows:
[0067] r = [W / (n × 1000 × ρ × π)] 1 / 2 ×1000;
[0068] Wherein, r is in μm; W is the fiber mass of the 1m long polyacrylonitrile fiber tow sample after dissolution treatment, and the polyacrylonitrile fiber tow to be characterized is nk tow; nk means that there are n×1000 single fibers in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 .
[0069] Among them, the calculation formula of the fiber radius r0 of the polyacrylonitrile fiber tow sample before dissolution treatment is as follows:
[0070] r0=[X m / (n×1000×ρ×π)] 1 / 2 ×1000;
[0071] Where, r0 is in μm; Xm is the weight of a 1m-long polyacrylonitrile fiber tow sample in grams; the polyacrylonitrile fiber tow to be characterized is nk tow; nk means there are n×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 .
[0072] The calculation formula for the dissolution depth H of each polyacrylonitrile fiber tow sample after dissolution treatment is as follows:
[0073] H = r0-r;
[0074] Wherein, r0 is the fiber radius of the polyacrylonitrile fiber tow sample before dissolution treatment;
[0075] r is the fiber radius of the polyacrylonitrile fiber tow sample after dissolution treatment.
[0076] Step 2): According to the relationship between the dissolution depth H and the dissolution treatment time t, the cortical thickness of the polyacrylonitrile fiber is determined.
[0077] In this step: draw a scatter plot of the dissolution depth (H) versus dissolution time (t) (e.g. Figure 1 as shown); according to the distribution of scattered points (data points) in the scatter plot, fit a straight line to the data points in the early stage of dissolution, and fit a straight line to the data points in the late stage of dissolution; determine the intersection of the two fitted straight lines, and record the coordinates of the intersection; determine the dissolution depth corresponding to the intersection as the cortical thickness.
[0078] In summary, compared with direct observation methods such as scanning electron microscopy and transmission electron microscopy, the characterization method of the skin-core structure of polyacrylonitrile fiber proposed in the present invention has the advantages of (1) simple operation, convenient and quick acquisition of skin thickness data, and timely guidance of process debugging; (2) the experimental equipment used in the method of the present invention is simple, requiring only a constant temperature water bath oscillator, several conical flasks and other simple devices, and the equipment cost is low.
[0079] The present invention is further described below by specific experimental examples:
[0080] The wet spinning adjustment coagulation molding process provides three polyacrylonitrile fibers in different process states, and the three fibers are numbered A, B, and C. The specifications of the three fibers are all 3K. Examples 1-3 respectively characterize the skin-core structures of the three specifications of polyacrylonitrile fibers.
[0081] Example 1
[0082] This embodiment is used to characterize the skin-core structure of a 3K polyacrylonitrile fiber tow numbered A, and mainly includes the following steps:
[0083] 1) Take ten samples (i.e., ten polyacrylonitrile fiber tow samples) from the polyacrylonitrile fiber tow numbered A, each sample is 1 m long, and the mass of the ten samples is within the range of 0.370±0.0015 g / m. The ten samples are marked as: 1#, 2#, 3#, 4#, 5#, 6#, 7#, 8#, 9#, 10#. Then, cut the ten samples into 2-3 cm lengths and open the fibers manually.
[0084] 2) The ten polyacrylonitrile fiber bundle samples were placed in a forced air drying oven, dried at 110° C. for 2 h, and then cooled.
[0085] 3) Prepare ten 500ml Erlenmeyer flasks, and place the 1#, 2#, 3#, 4#, 5#, 6#, 7#, 8#, 9#, and 10# polyacrylonitrile fiber tow samples in the ten Erlenmeyer flasks respectively; add 200mL of DMSO to each of the ten Erlenmeyer flasks, and shake them in a constant temperature (25°C) shaker for dissolution treatment. Different polyacrylonitrile fiber tow samples have different dissolution treatment times t.
[0086] Specifically, the dissolution treatment time of the 1# polyacrylonitrile fiber tow sample is 1 min; the dissolution treatment time of the 2# polyacrylonitrile fiber tow sample is 2 min; the dissolution treatment time of the 3# polyacrylonitrile fiber tow sample is 3 min; the dissolution treatment time of the 4# polyacrylonitrile fiber tow sample is 4 min. The dissolution treatment time of the 5# polyacrylonitrile fiber tow sample is 5 min; the dissolution treatment time of the 6# polyacrylonitrile fiber tow sample is 10 min; the dissolution treatment time of the 7# polyacrylonitrile fiber tow sample is 15 min; the dissolution treatment time of the 8# polyacrylonitrile fiber tow sample is 20 min; the dissolution treatment time of the 9# polyacrylonitrile fiber tow sample is 25 min; and the dissolution treatment time of the 10# polyacrylonitrile fiber tow sample is 30 min.
[0087] 4) After the dissolution treatment, the ten polyacrylonitrile fiber tow samples were taken out and washed with DMSO aqueous solutions of 88%, 55%, and 30% by mass for 1 minute, and finally washed with running water at room temperature for more than 10 minutes. Then, they were dried in an oven at 110°C for 2 hours, and after cooling, the weight W of the residual tow (i.e., the weight W of the polyacrylonitrile fiber tow sample after the dissolution treatment) was weighed.
[0088] The weights of the ten polyacrylonitrile fiber tow samples after dissolution treatment are recorded as W1 (0.345 g), W2 (0.342 g), W3 (0.334 g), W4 (0.331 g), W5 (0.304 g), W6 (0.246 g), W7 (0.114 g), W8 (0.071 g), W9 (0.028 g), W10 (0.036 g), W11 (0.042 g), W12 (0.036 g), W13 (0.053 g), W14 (0.062 g), W15 (0.071 g), W16 (0.083 g), W17 (0.091 g), W18 (0.092 g), W19 (0.014 g), W20 (0.015 g), W21 (0.016 g), W22 (0.01 10 (0.005g);
[0089] Then, the fiber radius r of the ten polyacrylonitrile fiber tow samples after dissolution treatment was calculated according to the following formula; the fiber radius r of the ten polyacrylonitrile fiber tow samples after dissolution treatment was recorded as: r1 (5.55 μm), r2 (5.52 μm), r3 (5.46 μm), r4 (5.43 μm), r5 (5.21 μm), r6 (4.68 μm), r7 (3.19 μm) 、 R8(2.51μm), R9(1.59μm), R 10 (0.7 μm);
[0090] r = [W / (3×1000×ρ×π)] 1 / 2 ×1000.
[0091] Where r is in μm; W is the fiber mass of a 1m long 3K polyacrylonitrile fiber bundle sample after dissolution treatment, 3K means there are 3×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber bundle sample, in g / cm 3 , specifically 1.19 g / cm 3 .
[0092] The fiber radius r0 of the polyacrylonitrile fiber tow sample before dissolution treatment was calculated by the following formula:
[0093] r0=[X m / (3×1000×ρ×π)] 1 / 2 ×1000;
[0094] Among them, r0 is in μm; X m is the weight of a 1m long 3K polyacrylonitrile fiber tow sample in grams, 3K means there are 3×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 , specifically 1.19 g / cm 3 .
[0095] In this embodiment, the 3K polyacrylonitrile fiber tow sample X m The value is 0.370g / m.
[0096] The dissolution depth of each polyacrylonitrile fiber tow sample in the radial direction was calculated by the following formula:
[0097] H=r0-r.
[0098] The dissolution depths of the ten polyacrylonitrile fiber tow samples after dissolution are as follows: H1 (0.20 μm), H2 (0.23 μm), H3 (0.29 μm), H4 (0.32 μm), H5 (0.54 μm), H6 (1.07 μm), H7 (2.56 μm), H8 (3.24 μm), H9 (4.16 μm), H10 (5.87 μm), H11 (6.37 μm), H12 (7.73 μm), H13 (8.97 μm), H14 (9.13 μm), H15 (10.25 μm), H16 (11.37 μm), H17 (12.97 μm), H18 (13.25 μm), H19 (14.13 μm), H20 (15.25 μm), H21 (15.25 μm), H22 (15.25 μm), H23 (15.25 μm), H24 (15.25 μm), H25 10 (5.05μm).
[0099] 5) In a rectangular coordinate system, a scatter plot (data points) is drawn showing the variation of dissolution depth (H) with dissolution treatment time (t); according to the distribution of the scatter plot points (data points), a straight line is fitted to the data points in the early dissolution period (dissolution treatment time ≤ 5 min), and a straight line is fitted to the data points in the late dissolution period (dissolution treatment time > 5 min); the intersection of the two fitted straight lines is determined, and the coordinates of the intersection are recorded; the dissolution depth corresponding to the intersection is determined as the cortical thickness.
[0100] The dissolution depth (H) of this embodiment varies with the dissolution time (t) as shown in Figure 2 As shown, the determined cortex thickness of the polyacrylonitrile fiber tow sample numbered A is shown in Table 1.
[0101] Example 2
[0102] This embodiment is used to characterize the skin-core structure of a 3K polyacrylonitrile fiber tow numbered B, and mainly includes the following steps:
[0103] 1) Take ten samples (i.e., ten polyacrylonitrile fiber tow samples) from the polyacrylonitrile fiber tow numbered B, each sample is 1 m long, and the mass of the ten samples is within the range of 0.370±0.0015 g / m. The ten samples are marked as: 1#, 2#, 3#, 4#, 5#, 6#, 7#, 8#, 9#, 10#. Then, cut the ten samples into 2-3 cm lengths and open the fibers manually.
[0104] 2) The ten polyacrylonitrile fiber bundle samples were placed in a forced air drying oven, dried at 110° C. for 2 h, and then cooled.
[0105] 3) Prepare ten 500ml Erlenmeyer flasks, and place the 1#, 2#, 3#, 4#, 5#, 6#, 7#, 8#, 9#, and 10# polyacrylonitrile fiber tow samples in the ten Erlenmeyer flasks respectively; add 200mL DMSO to each of the ten Erlenmeyer flasks, and shake them in a constant temperature (25°C) shaker for dissolution treatment. Different polyacrylonitrile fiber tow samples have different dissolution treatment times t.
[0106] Specifically, the dissolution treatment time of the 1# polyacrylonitrile fiber tow sample is 1 min; the dissolution treatment time of the 2# polyacrylonitrile fiber tow sample is 2 min; the dissolution treatment time of the 3# polyacrylonitrile fiber tow sample is 3 min; the dissolution treatment time of the 4# polyacrylonitrile fiber tow sample is 4 min. The dissolution treatment time of the 5# polyacrylonitrile fiber tow sample is 5 min; the dissolution treatment time of the 6# polyacrylonitrile fiber tow sample is 10 min; the dissolution treatment time of the 7# polyacrylonitrile fiber tow sample is 15 min; the dissolution treatment time of the 8# polyacrylonitrile fiber tow sample is 20 min; the dissolution treatment time of the 9# polyacrylonitrile fiber tow sample is 25 min; and the dissolution treatment time of the 10# polyacrylonitrile fiber tow sample is 30 min.
[0107] 4) After the dissolution treatment, the ten polyacrylonitrile fiber tow samples were taken out and washed with DMSO aqueous solutions of 88%, 55%, and 30% by mass for 1 minute, and finally washed with running water at room temperature for more than 10 minutes. Then, they were dried in an oven at 110°C for 2 hours, and after cooling, the weight W of the residual tow (i.e., the weight W of the polyacrylonitrile fiber tow sample after the dissolution treatment) was weighed.
[0108] The weights of the ten polyacrylonitrile fiber tow samples after dissolution treatment are recorded as W1 (0.340 g), W2 (0.329 g), W3 (0.322 g), W4 (0.305 g), W5 (0.274 g), W6 (0.144 g), W7 (0.062 g), W8 (0.02 g), W9 (0.004 g), W10 (0.006 g), W11 (0.008 g), W12 (0.009 g), W13 (0.010 g), W14 (0.011 g), W15 (0.008 g), W16 (0.009 g), W17 (0.011 g), W18 (0.008 g), W19 (0.009 g), W20 (0.008 g), W21 (0.009 g), W22 (0.008 10 (**g);
[0109] Then, the fiber radius r of the ten polyacrylonitrile fiber tow samples after dissolution treatment was calculated according to the following formula; the fiber radius r of the ten polyacrylonitrile fiber tow samples after dissolution treatment was recorded as: r1 (5.51 μm), r2 (5.42 μm), r3 (5.36 μm), r4 (5.22 μm), r5 (4.94 μm), r6 (3.58 μm), r7 (2.35 μm) 、 R8(1.35μm), R9(0.63μm), R 10 (**μm);
[0110] r = [W / (3×1000×ρ×π)] 1 / 2 ×1000.
[0111] Where r is in μm; W is the fiber mass of a 1m long 3K polyacrylonitrile fiber bundle sample after dissolution treatment, 3K means there are 3×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber bundle sample, in g / cm 3 , specifically 1.19 g / cm 3 .
[0112] The fiber radius r0 of the polyacrylonitrile fiber tow sample before dissolution treatment was calculated by the following formula:
[0113] r0=[X m / (3×1000×ρ×π)] 1 / 2 ×1000;
[0114] Among them, r0 is in μm; X m is the weight of a 1m long 3K polyacrylonitrile fiber tow sample in grams, 3K means there are 3×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm3 , specifically 1.19 g / cm 3 .
[0115] In this embodiment, the Xm value of the 3K fiber sample is 0.370 g / m.
[0116] The dissolution depth of each polyacrylonitrile fiber tow sample in the radial direction was calculated by the following formula:
[0117] H=r0-r.
[0118] The dissolution depths of the ten polyacrylonitrile fiber tow samples after dissolution are recorded as follows: H1 (0.24 μm), H2 (0.33 μm), H3 (0.39 μm), H4 (0.53 μm), H5 (0.81 μm), H6 (2.17 μm), H7 (3.4 μm), H8 (4.4 μm), H9 (5.12 μm), H10 (6.8 μm), H11 (7.9 μm), H12 (8.3 μm), H13 (9.7 μm), H14 (15.3 μm), H15 (16.7 μm), H16 (17.9 μm), H17 (20.7 μm), H18 (21.3 μm), H19 (23.7 μm), H20 (24.7 μm), H21 (25.9 μm), H22 (26.8 μm), H23 (27.8 μm), H24 (28.9 μm), H25 (29.9 μm), 10 (**μm).
[0119] 5) In a rectangular coordinate system, a scatter plot (data points) is drawn showing the variation of dissolution depth (H) with dissolution treatment time (t); according to the distribution of the scatter plot points (data points), a straight line is fitted to the data points in the early dissolution period (dissolution treatment time ≤ 5 min), and a straight line is fitted to the data points in the late dissolution period (dissolution treatment time > 5 min); the intersection of the two fitted straight lines is determined, and the coordinates of the intersection are recorded; the dissolution depth corresponding to the intersection is determined as the cortical thickness.
[0120] The dissolution depth (H) of this embodiment varies with the dissolution time (t) as shown in Figure 1 . As shown, the cortex thickness of the polyacrylonitrile fiber tow sample numbered B is shown in Table 1.
[0121] Example 3
[0122] This embodiment is used to characterize the skin-core structure of a 3K polyacrylonitrile fiber tow numbered C, and mainly includes the following steps:
[0123] 1) Take ten samples (i.e., ten polyacrylonitrile fiber tow samples) from the polyacrylonitrile fiber tow numbered C, each sample is 1 m long, and the mass of the ten samples is within the range of 0.370±0.0015 g / m. The ten samples are marked as: 1#, 2#, 3#, 4#, 5#, 6#, 7#, 8#, 9#, 10#. Then, cut the ten samples into 2-3 cm lengths and open the fibers manually.
[0124] 2) The ten polyacrylonitrile fiber bundle samples were placed in a forced air drying oven, dried at 110° C. for 2 h, and then cooled.
[0125] 3) Prepare ten 500ml Erlenmeyer flasks, and place the 1#, 2#, 3#, 4#, 5#, 6#, 7#, 8#, 9#, and 10# polyacrylonitrile fiber tow samples in the ten Erlenmeyer flasks respectively; add 200mL DMSO to each of the ten Erlenmeyer flasks, and shake them in a constant temperature (25°C) shaker for dissolution treatment. Different polyacrylonitrile fiber tow samples have different dissolution treatment times t.
[0126] Specifically, the dissolution treatment time of the 1# polyacrylonitrile fiber tow sample is 1 min; the dissolution treatment time of the 2# polyacrylonitrile fiber tow sample is 2 min; the dissolution treatment time of the 3# polyacrylonitrile fiber tow sample is 3 min; the dissolution treatment time of the 4# polyacrylonitrile fiber tow sample is 4 min. The dissolution treatment time of the 5# polyacrylonitrile fiber tow sample is 5 min; the dissolution treatment time of the 6# polyacrylonitrile fiber tow sample is 10 min; the dissolution treatment time of the 7# polyacrylonitrile fiber tow sample is 15 min; the dissolution treatment time of the 8# polyacrylonitrile fiber tow sample is 20 min; the dissolution treatment time of the 9# polyacrylonitrile fiber tow sample is 25 min; and the dissolution treatment time of the 10# polyacrylonitrile fiber tow sample is 30 min.
[0127] 4) After the dissolution treatment, the ten polyacrylonitrile fiber tow samples were taken out and washed with DMSO aqueous solutions of 88%, 55%, and 30% by mass for 1 minute, and finally washed with running water at room temperature for more than 10 minutes. Then, they were dried in an oven at 110°C for 2 hours, and after cooling, the weight W of the residual tow (i.e., the weight W of the polyacrylonitrile fiber tow sample after the dissolution treatment) was weighed.
[0128] The weights of the ten polyacrylonitrile fiber tow samples after dissolution treatment are recorded as W1 (0.340 g), W2 (0.328 g), W3 (0.322 g), W4 (0.300 g), W5 (0.289 g), W6 (0.161 g), W7 (0.073 g), W8 (0.038 g), W9 (0.005 g), W10 (0.006 g), W11 (0.007 g), W12 (0.008 g), W13 (0.009 g), W14 (0.010 g), W15 (0.011 g), W16 (0.012 g), W17 (0.013 g), W18 (0.014 g), W19 (0.008 g), W20 (0.009 g), W21 (0.008 g), W22 (0.00 10 (**g);
[0129] Then, the fiber radius r of the ten polyacrylonitrile fiber tow samples after dissolution treatment was calculated according to the following formula; the fiber radius r of the ten polyacrylonitrile fiber tow samples after dissolution treatment was recorded as: r1 (5.51 μm), r2 (5.41 μm), r3 (5.36 μm), r4 (5.17 μm), r5 (5.08 μm), r6 (3.79 μm), r7 (2.55 μm) 、 R8(1.84μm), R9(0.65μm), R 10 (**μm);
[0130] r = [W / (3×1000×ρ×π)] 1 / 2 ×1000.
[0131] Where r is in μm; W is the fiber mass of a 1m long 3K polyacrylonitrile fiber bundle sample after dissolution treatment, 3K means there are 3×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber bundle sample, in g / cm 3 , specifically 1.19 g / cm 3 .
[0132] The fiber radius r0 of the polyacrylonitrile fiber tow sample before dissolution treatment was calculated by the following formula:
[0133] r0=[X m / (3×1000×ρ×π)] 1 / 2 ×1000;
[0134] Among them, r0 is in μm; X m is the weight of a 1m long 3K polyacrylonitrile fiber tow sample in grams, 3K means there are 3×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 , specifically 1.19 g / cm 3 .
[0135] In this embodiment, the Xm value of the 3K fiber sample is 0.370 g / m.
[0136] The dissolution depth of each polyacrylonitrile fiber tow sample in the radial direction was calculated by the following formula:
[0137] H=r0-r.
[0138] The dissolution depths of the ten polyacrylonitrile fiber tow samples after dissolution are recorded as follows: H1 (0.24 μm), H2 (0.34 μm), H3 (0.39 μm), H4 (0.58 μm), H5 (0.67 μm), H6 (1.96 μm), H7 (3.20 μm), H8 (3.91 μm), H9 (5.10 μm), H10 (5.70 μm), H11 (5.97 μm), H12 (5.83 μm), H13 (5.97 μm), H14 (5.83 μm), H15 (5.97 μm), H16 (5.83 μm), H17 (5.97 μm), H18 (5.83 μm), H19 (5.83 μm), H20 (5.83 μm), H21 (5.83 μm), H22 ( 10 (**μm).
[0139] 5) In a rectangular coordinate system, a scatter plot (data points) is drawn showing the variation of dissolution depth (H) with dissolution treatment time (t); according to the distribution of the scatter plot points (data points), a straight line is fitted to the data points in the early dissolution period (dissolution treatment time ≤ 5 min), and a straight line is fitted to the data points in the late dissolution period (dissolution treatment time > 5 min); the intersection of the two fitted straight lines is determined, and the coordinates of the intersection are recorded; the dissolution depth corresponding to the intersection is determined as the cortical thickness.
[0140] The dissolution depth (H) of this embodiment varies with the dissolution time (t) as shown in Figure 3 . As shown, the cortex thickness of the polyacrylonitrile fiber tow sample numbered C is determined as shown in Table 1.
[0141] Table 1 shows the skin thickness of polyacrylonitrile fibers numbered A, B, and C in Examples 1-3, as follows:
[0142] Table 1
[0143] Fiber No. Cortical thickness (μm) A 0.32 B 0.42 C 0.67
[0144] Comparative Example 1
[0145] The polyacrylonitrile fiber tow sample used in Comparative Example 1 is the same as that in Example 3.
[0146] The polyacrylonitrile fiber tow sample of comparative example 1 is obtained by wet spinning. The wet-spun fiber has a cortical structure, which will form a porous layer on the surface of the polyacrylonitrile-based carbon fiber finally obtained after subsequent pre-oxidation and high-temperature carbonization. The thickness of the porous layer can be obtained by directly observing the porous layer on the surface of the carbon fiber cross section through TEM. The shrinkage rate of the diameter during the conversion of the polyacrylonitrile fiber tow sample into carbon fiber can be converted to obtain the cortical thickness of the polyacrylonitrile sample of this comparative example.
[0147] The polyacrylonitrile fiber tow sample of comparative example 1 was subjected to conventional pre-oxidation and carbonization treatment to obtain the corresponding polyacrylonitrile-based carbon fiber. Single fibers were randomly selected from the carbon fiber tow, and single fiber cross-section samples (cross-section thickness required to be ≤100 nm) were prepared using FIB-SEM and focused ion beam thinning technology, and then HRTEM (high resolution TEM) was used to observe the cross-section samples. Figure 4 This is a cross-sectional TEM photograph of a carbon fiber monofilament prepared using the polyacrylonitrile fiber tow sample of Comparative Example 1. Figure 4 It can be clearly seen that there is a porous layer on the surface of the circular cross section of the monofilament, and the thickness of the porous layer is about 0.39 μm.
[0148] After conventional pre-oxidation and carbonization, the fiber cross section will shrink. Generally speaking, the ratio of the diameter of the polyacrylonitrile fiber monofilament to the diameter of the corresponding carbon fiber monofilament is 1.67:1 (obtained from statistical analysis of process practice). According to this direct shrinkage ratio, the cortical thickness of the polyacrylonitrile sample can be converted based on the pore layer thickness obtained from the TEM photo. The cortical thickness of the sample in this comparative example is 1.67×0.39=0.65μm.
[0149] The polyacrylonitrile fiber bundle sample of Comparative Example 1 is the same as the polyacrylonitrile fiber bundle sample of Example 3. The cortical thickness of the polyacrylonitrile fiber bundle sample obtained by the method of Comparative Example 1 is basically the same as the cortical thickness obtained in Example 3, which shows the accuracy of the characterization method of the present invention.
[0150] Compared with Comparative Example 1, the beneficial effects of the present invention are as follows:
[0151] (1) The method of comparative example 1 has the disadvantages of high sample preparation and testing costs and long testing cycle (FIB-SEM and ion thinning costs are high, HRTEM observation costs are high, and the testing cycle is at least 1 month). The overall testing cost of the method of the present invention is extremely low and can be carried out in a conventional laboratory. At the same time, the testing cycle is short, which is convenient for timely feedback of process debugging;
[0152] (2) Comparative Example 1 is a single-filament sample preparation, and the data finally obtained often only reflects the cortical thickness of the single-filament, which is difficult to represent the average cortical level of a 3k tow (3000 single filaments). The method of the present invention can obtain the average cortical thickness of the bundle, which is more representative of the average cortical level of the bundle.
[0153] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for characterizing the skin-core structure of polyacrylonitrile fiber, characterized in that: It includes the following steps: Step 1): taking a plurality of polyacrylonitrile fiber tow samples of a set length from the polyacrylonitrile fiber tow to be characterized; performing a dissolution treatment on the plurality of polyacrylonitrile fiber tow samples, wherein different polyacrylonitrile fiber tow samples have different corresponding dissolution treatment times t; and calculating the dissolution depth H of each polyacrylonitrile fiber tow sample after the dissolution treatment; Step 2): According to the relationship between the dissolution depth H and the dissolution treatment time t, the cortical thickness of the polyacrylonitrile fiber is determined.
2. The method for characterizing the skin-core structure of polyacrylonitrile fiber according to claim 1, characterized in that: In the step 1): The calculation formula of the dissolution depth H is as follows: H=r0-r; Wherein, r0 is the fiber radius of the polyacrylonitrile fiber tow sample before dissolution treatment; r is the fiber radius of the polyacrylonitrile fiber tow sample after dissolution treatment.
3. The method for characterizing the skin-core structure of polyacrylonitrile fiber according to claim 2, characterized in that: The calculation formula of r0 is as follows: r0=[X m / (n×1000×ρ×π)] 1 / 2 ×1000; Among them, r0 is in μm; X m is the weight of a 1m long polyacrylonitrile fiber tow sample in grams; the polyacrylonitrile fiber tow to be characterized is nk tow; nk means there are n×1000 single filaments in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 .
4. The method for characterizing the sheath-core structure of polyacrylonitrile fiber according to claim 2, characterized in that: The calculation formula of r is as follows: r=[W / (n×1000×ρ×π)] 1 / 2 ×1000; Wherein, r is in μm; W is the fiber mass of the 1m long polyacrylonitrile fiber tow sample after dissolution treatment, and the polyacrylonitrile fiber tow to be characterized is nk tow; nk means that there are n×1000 single fibers in a bundle of fibers; ρ is the density of the polyacrylonitrile fiber tow sample, in g / cm 3 .
5. The method for characterizing the sheath-core structure of polyacrylonitrile fiber according to any one of claims 1 to 4, characterized in that: The step 1) comprises: Step 11): taking a plurality of polyacrylonitrile fiber tow samples of a set length from the polyacrylonitrile-based fiber tow to be characterized; Step 12): drying a plurality of polyacrylonitrile fiber tow samples; after cooling, placing the plurality of polyacrylonitrile fiber tow samples in different dissolution containers, adding a set amount of solvent into each dissolution container, and dissolving them; wherein different polyacrylonitrile fiber tow samples have different dissolution treatment times; preferably, the mass ratio of the solvent to the polyacrylonitrile fiber tow sample is (400-600):1; Step 13) After reaching the corresponding dissolution treatment time, washing, drying, cooling, and weighing the fibers of each polyacrylonitrile fiber tow sample after the dissolution treatment to obtain the fiber mass W of each polyacrylonitrile fiber tow sample after the dissolution treatment; Step 14) according to the fiber mass W of the polyacrylonitrile fiber tow sample after the dissolution treatment, respectively calculate the fiber radius r of each polyacrylonitrile fiber tow sample after the dissolution treatment, and further calculate the dissolution depth H of each polyacrylonitrile fiber tow sample after the dissolution treatment; Preferably, in step 12), the solvent is selected from one or more of dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and dimethylacetamide (DMAc); Preferably, in step 12), during the dissolution treatment, the dissolution container needs to be placed in a constant temperature shaker at 25-30° C. for shaking; Preferably, in step 12), the drying temperature is 105-120° C., and the drying time is 1.5-3 h; Preferably, in step 13), when washing, first wash with an aqueous solution of DMSO and then wash with running water; Preferably, in step 13), the drying temperature is 105-120° C., and the drying time is 2-4 hours.
6. The method for characterizing the skin-core structure of polyacrylonitrile fiber according to claim 5, characterized in that: In the step 11): The polyacrylonitrile fiber tow to be characterized is an n K tow, where n K means there are n×1000 single filaments in one fiber tow. A tow with a length of 0.1-1 m is taken from the polyacrylonitrile fiber tow to be characterized as a polyacrylonitrile fiber tow sample; Preferably, the larger the n value is, the smaller the length of the polyacrylonitrile fiber tow sample is; Preferably, a tow with a length of 0.5-1 m is taken as the polyacrylonitrile fiber tow sample; Preferably, before the dissolution treatment, the polyacrylonitrile fiber tow sample needs to be cut into segments of 2-3 cm in length and manually opened.
7. The method for characterizing the sheath-core structure of polyacrylonitrile fiber according to any one of claims 1 to 6, characterized in that: In the step 12), the dissolution treatment time ranges from 1 to 30 minutes.
8. The method for characterizing the sheath-core structure of polyacrylonitrile fiber according to any one of claims 1 to 7, characterized in that: A plurality of polyacrylonitrile fiber tow samples of set lengths include a first polyacrylonitrile fiber tow sample, a second polyacrylonitrile fiber tow sample, a third polyacrylonitrile fiber tow sample, a fourth polyacrylonitrile fiber tow sample, a fifth polyacrylonitrile fiber tow sample, a sixth polyacrylonitrile fiber tow sample, a seventh polyacrylonitrile fiber tow sample, an eighth polyacrylonitrile fiber tow sample, a ninth polyacrylonitrile fiber tow sample, and a tenth polyacrylonitrile fiber tow sample; wherein, The dissolution treatment time corresponding to the first polyacrylonitrile fiber tow sample is 1-1.2 min, preferably 1 min; the dissolution treatment time corresponding to the second polyacrylonitrile fiber tow sample is 2-2.2 min, preferably 2 min; the dissolution treatment time corresponding to the third polyacrylonitrile fiber tow sample is 3-3.2 min, preferably 3 min; the dissolution treatment time corresponding to the fourth polyacrylonitrile fiber tow sample is 4-4.2 min, preferably 4 min; the dissolution treatment time corresponding to the fifth polyacrylonitrile fiber tow sample is 5-5.2 min, preferably 5 min; the dissolution treatment time corresponding to the sixth polyacrylonitrile fiber tow sample is 5-6 min, preferably 5 min; The dissolution treatment time corresponding to the polyacrylonitrile fiber tow sample is 10-10.5min, preferably 10min; the dissolution treatment time corresponding to the seventh polyacrylonitrile fiber tow sample is 15-15.5min, preferably 15min; the dissolution treatment time corresponding to the eighth polyacrylonitrile fiber tow sample is 20-21min, preferably 20min; the dissolution treatment time corresponding to the ninth polyacrylonitrile fiber tow sample is 25-26min, preferably 25min; the dissolution treatment time corresponding to the tenth polyacrylonitrile fiber tow sample is 29-30min, preferably 30min.
9. The method for characterizing the skin-core structure of polyacrylonitrile fiber according to any one of claims 1 to 8, characterized in that: The step 2) comprises: Step 21): In a rectangular coordinate system, plotting a data point diagram of the dissolution depth H as a function of the dissolution treatment time t; Step 22): according to the distribution of the data points, the data points at the early stage of dissolution are fitted into a first straight line, and the data points at the late stage of dissolution are fitted into a second straight line; Step 23): determine the intersection of the first straight line and the second straight line, and record the coordinates of the intersection; determine the value of the dissolution depth corresponding to the intersection as the cortical thickness of the polyacrylonitrile fiber tow to be characterized.
10. The method for characterizing the sheath-core structure of polyacrylonitrile fiber according to claim 9, characterized in that: In the step 22): Preferably, when fitting the data points into the first straight line and the second straight line, the dissolution treatment time range corresponding to the initial dissolution stage and the dissolution treatment time range corresponding to the late dissolution stage are determined according to the distribution characteristics of the data points; Preferably, the data points at the initial stage of dissolution refer to data points corresponding to a dissolution treatment time t in the range of ≤5 min; the data points at the late stage of dissolution refer to data points corresponding to a dissolution treatment time t in the range of greater than >5 min and ≤30 min.
Citation Information
Patent Citations
Polyacrylonitrile preoxidized fiber skin-core structure detection method
CN106596614A
Polyacrylonitrile fiber, polyacrylonitrile-based carbon fiber and preparation method of polyacrylonitrile fiber
CN110093677A
Polyester monofilament for woven and knit fabric
JP2010222771A
Method for determining chemical composition and thickness of two-layer electroplated coating
RU2759632C1
Continuous single layer film structure including discrete domains
US20140271787A1
Cited By
Method for measuring skin-core rate
CN121113918A
